Effective stabilization of a planar phosphorus(iii) center embedded in a porphyrin-based fused aromatic skeleton. Issue 12 (17th October 2017) - Fujimoto, Keisuke; Osuka, Atsuhiro
Abstract : Planar phosphorus(iii ) centers were effectively stabilized by structural constraint as well as aromatic stabilization in porphyrin-based fused π-conjugated frameworks. Abstract : Organophosphorus(iii ) compounds usually take on stable pyramidal structures with a large inversion barrier of 30–35 kcal mol −1 . In contrast, diphenylphosphine-fused Ni(ii ) porphyrin, where the phosphorus atom is directly attached at the meso-position and embedded in a rigid skeleton, exhibits a considerably planarized phosphorus center. Here we report the synthesis of a mesityl-substituted Ni(ii ) porphyrin analogue, 6, which allowed an evaluation of the inversion barrier (Δ G ‡203) by variable temperature 1 H NMR spectroscopy which showed it to be exceptionally small, at 14.0 kcal mol −1 . The observed small inversion barrier has been attributed to conformational constraint imposed by the fused structure. In addition, it was thought that the planar transition state is stabilized by the Ni(ii ) porphyrin network that allows the contribution of a 22π-aromatic circuit involving phosphorus lone-pair electrons. Along this postulate, we attempted to engineer diarylphosphine-fused porphyrins with smaller inversion barriers by replacing the fused benzene rings with five-membered heterocyclic rings such as thiophene, benzothiophene, benzofuran, indole, benzothiophene 1, 1-dioxide, and thiophene 1, 1-dioxide. In that order, the aromatic character of the heterocycle decreases, which leads to increasing contribution of the 22π-aromatic circuit. Actually, the inversion barrier of the phosphorus center becomes smaller in this order and reaches 8.7 kcal mol −1 for thiophene 1, 1-dioxide-fused Ni(ii ) porphyrin15, supporting the postulate.